(3eQMdI GdJMbjb GdGHJOGFj ddOYhi GdLfGFjI CeGe GdeMceI GdLfGFjI GdOhdjI GdOGFeI (B/ s - (3aJMj Ydi eMeO GdSjOs; (3MSfjf EHQGgje UGdM YHjO (B: s ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2015)
(3JJYdb gPg GdOQGSI HehVhY(B: "(3eQMdI GdJMbjb GdGHJOGFj ddOYhi GdLfGFjI CeGe GdeMceI GdLfGFjI GdOhdjI GdOGFeI(B": (3HeG JeKdg ef BdjGJ hELQGAGJ hCMcGe; eeG jYfj NQhL CMcGe hELQGAGJ SjQ GdOYhi GdLfGFjI CeGe GdeMceI aj eQMdI GdeMGceI Yf fWGb GdHMK(B. (3h jeKd gPG GdehVhY CgejI HGdZI dhLhO YOI CSHGH dYd CHQRgG(B: (3TOI JYdb Ch eSGS GdELQGAGJ GdefVhjI aj gPg GdeQMdI HMbhb GdCTNGU eMd GdJMbjb hGdGJgGe hMQjGJge(B: (3hef Ke HMbhb GdEfSGf HUaI YGeI(B. (3HGdEVGaI Edi OhQgG aj JMbjb GdYOGdI GdLfGFjI GdOhdjI(B: (3hEfUGa GdeLfj Ydjge hGdVMGjG(B: (3aj ehGLgI CTO GdLQGFe GdOhdjI LSGeI; ceG Cf GdeSGFd Ch GdETcGdjGJ GdJj JQJHW HehVhY GdeMceI GdLfGFjI GdOhdjI HOpbgG hoLdgG(B: (3hGdJj bO jWGd HYVgG eQMdI GdeMGceI(B: (3fSJWjY Cf fdeS JCKjQgG Ydj ELQGAGJ SjQ GdJMbjb GdGHJOGFj ddOYhi GdLfGFjI CeGe GdeMceI HUhQI eHGTQI Ch ZjQ eHGTQIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi (B2015s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdOGFQI GdJegjOjIs; (3GdeMceI GdLfGFjI GdOhdjIs; (3GdeOYj GdYGes; (3QSGFd LGeYjIs